PECULIARITIES OF PHILOLOGY STUDENTS’ SUBJECT-MATTER COMPETENCES FORMATION TECHNOLOGY ADOPTION WHILE HUMANITARIAN DISCIPLINES STUDYING - Udovichenko, Hannah; Ostapenko, Svitlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article deals with the conceptual and pragmatic aspects of philological specialties students’ subject-matter competences formation technology adoption in the process of humanitarian disciplines studying. The aim of the article is to introduce the technology of philological specialties students’ subject-matter competences formation, corresponding to it didactic conditions. The technology consists of six stages (the stage of goal-setting and immersion, the stage of philological specialties students’ subject-matter competences successful formation motivational ensuring, the stage of educational information rationalization and didactic facilitation, the operational stage, the stage of promoting reflexive actions and the stage of determining correlations between the expected and the consequences of subject-matter formation, the self-presentation of the achieved. The varieties of educational activity, which were realized in six stages of the subject-matter competences formation technology based on parallel-concentric allocation, are presented.The research was conducted by applying the following methods: theoretical: analysis and synthesis of scientific, popular scientific, methodical and educational literature on the problems of higher school didactics and intensification of students’ training to research the specific use of competency approach as didactic paradigm; empirical: poll (questionnaire, interview) of students and faculty of humanities departments, monitoring the manifestation of the dynamics of students’ learning process ranking to identify best forms of educational work for the aim of solving research problems based on competence approach.It is determined that the main result of the development and adoption of philological specialties students’ subject-matter competences formation technology in the process of humanitarian disciplines studying is the increase of students' subject-matter competence formation level, provided that the technology and its corresponding didactic conditions are implemented in the educational process.